Pemanfaatan Google Workspace for Education dalam Pembelajaran di Kelas. Studi kasus di SMP Islam Dian Didaktika, Kota Depok - Akbar Akbar; Gayu Rahman Atmaja; Ibnu Aidil Putra (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2025)
Educational institutions must be able to provide innovation in every learning process to achieve quality education. The development of digital technology and the presence of Google Workspace for Education for learning are considered to make classroom learning activities more innovative and more effective, however, in reality, many educational institutions have not utilized technology optimally in learning activities. To address this problem, the author is interested in examining how Google Workspace for Education is utilized in classroom learning. This study aims to explore the use of Google Workspace for Education by teachers in creating innovative and effective learning. This research is a qualitative study using a case study. Data collection techniques through observation, documentation, and in-depth interviews. Data analysis techniques used in this study are data reduction, data presentation, and drawing conclusions. The results of this study indicate that the use of Google Workspace for Education in classroom learning makes learning more engaging and enriched with digital-based learning materials and media. These findings can serve as a reference for policymakers in designing programs to improve teachers' digital competencies. However, successful implementation depends heavily on the readiness of teachers' infrastructure, digital competencies, and appropriate learning management strategies.